A retrospective study of the epidemiology of leprosy in Cebu: an eleven-year profile. - Pauline F D Scheelbeek; Marivic V F Balagon; Florenda M Orcullo; Armi A Maghanoy; Junie Abellana; Paul R Saunderson (Public Library of Science (PLoS), 2013)
Cebu has been one of the most leprosy endemic areas in the Philippines. Despite the high coverage rates of multiple drug therapy (MDT) and high BCG-vaccine coverage in children, leprosy control authorities believe that leprosy transmission and incidence (as evidence by continuing new case detection in both adults and children) have not declined as expected, once leprosy had been eliminated. In response to the concerns communicated by the authorities regarding ongoing leprosy transmission in Cebu, this study aims to examine the evidence for the hypothesized ongoing transmission, both in children and adults. Furthermore, it will be assessed which groups and areas are experiencing a continuing risk of leprosy infection; this can form a starting point for more targeted approaches to leprosy control.Case records from 2000-2010 were retrospectively collected from the Leonard Wood Memorial Clinic archives, and all other clinics on the island where leprosy was treated. Between 2000 and 2010, 3288 leprosy cases were detected. The overall five year case notification rate (CNR) dropped significantly from 47.35 (2001-2005) to 29.21 cases (2006-2010) per 100.000 population. Smaller CNRs were reported for children; however the decline in child-CNR over the same period was minimal. Furthermore, no increase in median age of notification in children or adults was found between 2000 and 2010. Population-adjusted clustering of leprosy cases was mainly detected in urban and peri-urban areas.Although the overall CNR declined significantly, CNR seems to be rather static in lower risk populations and areas. Cases are mainly found in urban areas, however CNRs in these areas decline at a much faster rate than in the lower endemic rural areas. A similar situation was found when comparing adults and children: CNRs observed in children were lower than in adults, but further decline (and elimination) of these childhood CNRs was found to be difficult. Moreover, the median age of notification in children has remained stable, suggesting transmission is still on-going. It is unclear why many years of good MDT-coverage and a gradual decline in CNR have not been accompanied by evidence of reduced transmission, especially beyond a certain threshold level of case notification. We believe that a new approach to leprosy control is required to tackle transmission more directly. The most promising approach may involve chemoprophylaxis and/or immunoprophylaxis interventions, targeted at high risk (urban) areas and groups such as household contacts, followed by a different approach once decline in CNR starts to level off. Identified clusters and trends can form the starting point for implementing this approach.